Modeling the Process of Thawing of Tailings Dam Base Soils by Technological Waters - Nataliya Yurkevich; Irina Fadeeva; Elizaveta Shevko; Alexey Yannikov; Svetlana Bortnikova (Applied Sciences, 2021)
The storage of wastes from mining and mineral processing plants in the tailing dumps in regions with cold climates has a number of environmental consequences. Interactions of water with tailings in cold climates often lead to the thawing of permafrost soils, formation of technogenic thawing zones, and leakage of drainage waters. In the case of fault zones development in these areas, technogenic solutions are often filtered outside the tailing dump, promoting further development of filtration channels. In order to prevent leakage of solution from tailing dumps over time, it is necessary to determine the thawing zones and prevent the formation of filtration channels. In the case of the formation of a filtration channel, it is necessary to know what rate of rock thawing occurred near the formed filtration channel. In this study, for the tailing dump of a diamond mining factory, we calculated two exothermic effects: (1) due to physical heating of dump rock by filtering industrial water with temperatures from 2 to 15 °C through the rock; and (2) due to the chemical interaction of industrial water with the dam base rock. The amount of energy transferred by the water to the frozen and thawed rock over 10 years was calculated using thermophysical modeling and was 207.8 GJ and 8.39 GJ respectively. The amount of energy that the rock received during the ten-year period due to dissolution of the limestones and equilibration of solutions was calculated using thermodynamic modeling and was 0.37 GJ, which is 4.4% of the average amount of energy, expended on heating the thawed rock (8.39 GJ).